DEVELOPMENT OF QR CODE-BASED TV BOX MEDIA TO IMPROVE STUDENTS' MEMORY ABILITIES IN THE FIQH SUBJECT AT MTsN 1 TUBAN - Alfi Manzilatir Rohmah; Rr. Kusuma Dwi Nur Ma’rifat (Jurnal Bilqolam Pendidikan Islam, 2026)
The low memory capacity of students in the subject of Fiqh is one of the obstacles in achieving learning outcomes, especially in conceptual and procedural materials. This condition is influenced by the use of learning methods that are still monotonous and the lack of utilization of interactive learning media that can help students understand and remember the material optimally. As a result, students have difficulty in retaining the information that has been learned for a certain period of time. This study aims to develop a QR Code-based TV Box media as an interactive learning tool to improve retention or memory of grade VIII students at MTsN 1 Tuban in the subject of Fiqh. This study uses the Research and Development (R&D) method with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. The feasibility of the media was tested through validation by material experts and media experts, while the effectiveness of the media was analyzed using a pretest-posttest design with N-Gain calculations. The validation results showed that the media obtained a percentage of 87.27% from material experts and 99.00% from media experts with an overall average of 93.14% which is included in the very valid category. The effectiveness test showed an increase in the average student score from 62.4 in the pretest to 81.2 in the posttest with an N-Gain value of 0.5, which is in the moderate category. Furthermore, student response to the use of the media reached 87.14% and teacher response was 96.84%, both of which are in the very good category. The findings of this study prove that the integration of QR Code-based TV Box media can create more interactive, engaging, and effective Fiqh learning in strengthening students' memory.